Devil's knot [videorecording (DVD)] - Firth, Colin, 1960-; Witherspoon, Reese, 1976-; Ryan, Amy; Moyer, Stephen; Boardman, Paul Harris; Derrickson, Scott; Leveritt, Mara
In a gripping, heart-wrenching true story that shocked the nation. May 5, 1993. West Memphis, Arkansas. Three young boys playing in the nearby woods never come home for dinner. In the rush to find and convict the killers, police focus on a trio of teenagers suspected of devil worship. It is only when an investigator reveals that the evidence doesn't all add up, that the community is forced to face the reality that the true killer might still be out there.